Atom‐Efficient Route for Converting Incineration Ashes into Heavy Metal Sorbents. Issue 1 (12th December 2013) - Chiang, Yi Wai; Santos, Rafael M.; Vanduyfhuys, Kenneth; Meesschaert, Boudewijn; Martens, Johan A.
Abstract Bottom ashes produced from municipal solid‐waste incineration are suitable for sorbent synthesis because of their inherent composition, high alkalinity, metastable mineralogy, and residual heat. This work shows that bottom ashes can be atom‐efficiently converted into valuable sorbents without the need for costly and hazardous chemicals. The ashes were hydrothermally treated in rotary autoclaves at autogenic pH conditions to promote the conversion of precursor mineral phases into zeolites and layered silicate hydrates. Two main mineral phases were formed: katoite and sodium aluminum phosphate silicate hydrate. These mineral alterations are accompanied by a tenfold increase in specific surface area and a twofold reduction in average particle size. Performance evaluation of the new sorbents for Cd2+, Zn2+, and Pb2+ adsorption at pH 5 indicates sorption capacities of 0.06, 0.08, and 0.22 mmol g−1, respectively, which are similar to those of natural adsorbents and synthetic materials obtained from more demanding synthesis conditions.